P153 Measuring functional PI3K and NFkB pathway activity to distinguish between short-term and long-term disease-free survivors of high grade serous ovarian cancer. (1st November 2019) - van Lieshout, LAM; van de Stolpe, A; Bekkers, RLM; de Hullu, JA; Piek, JMJ
Abstract : Introduction/Background: The disease-free survival (DFS) of high-grade serous cancer (HGSC) varies greatly, despite comparable clinicopathological features and treatment. It is our hypothesis that the difference in DFS is caused by differences in activity of tumour-driving signal transduction pathways. Methodology: Using previously described Signal Transduction pathway Activity (STA) assays (table 1), signalling pathway activity scores for AR, ER, PI3K-FOXO, HH, NFkB, TGFβ, NOTCH and Wnt were derived from publicly available mRNA expression (Affymetrix) data of primary HGSC, with clinical annotation (GSE9891). K-means cluster analysis was performed on STA-scores of AR, ER, PI3K-FOXO, HH, NFkB, TGFB, NOTCH and Wnt pathway. However, as PI3K and NFkB scores were most discriminating in cluster formation, final clusters were based on these pathways alone. Results: We selected 81 out of 140 sample data with a DFS <12 or >24 months. The remaining 59 samples with a DFS of 12–24 months were kept aside to be allocated to identified clusters by discriminant analysis in a later stage. Repeated K-means clustering resulted in two stable clusters; a low PI3K/high FOXO and high NFkB cluster (n=43) with a more favourable prognosis, and a high PI3K/low FOXO and low NFkB cluster (n=38) with a less favourable prognosis (log-rank=0.011, figure 1). The remaining samples (n=59) were then allocated resulting in a low PI3K and high NFkB cluster of 73 samples, and a high PI3K and low NFkB cluster of 67 samples (log-rank=0.036, figure 2). Conclusion: We identified two signalling pathway activity clusters in HGSC with a difference in DFS. The low PI3K/high FOXO and high NFkB activity of the favourable prognosis cluster may indicate apoptosis, while the high PI3K/low FOXO and low NFkB activity of the unfavourable prognosis cluster may indicate high cell division. Elucidating underlying mechanisms of HGSC aids our understanding of the disease and provides possible new leads for targeted therapies. Disclosure: LvL has nothing to disclose, AvdS is employed by Philips Research, RB has nothing to disclose, JdH has nothing to disclose, JP has nothing to disclose. Funding granted by the Ruby& Rose fund and Catharina research fund.